MORPHOMETRIC ANALYSIS OF ANGIO-ARCHITECTURE OF THE CEREBELLA CORTEX UNDER THE EFFECT OF OPIOID INFLUENCE - Бекесевич, А.М. (World of Medicine and Biology, 2014)
Drug addiction has become a serious problem not only because of the progressing pathopsychological changes in drug using patients, but also because of the development of multiple polyorgan comorbid pathology, that together with the great economic and moral losses place the problem of drug addiction in the range of the most important problems in many countries of the world. Data on the development of pathological changes of the cerebellum under the influence of drugs are insufficient and need to be studied further on. Thus, cerebellum cortex hemomicrocirculatory bed after 6 weeks of injecting nalbufin appears at the stage of decompensation, when the capillary component is destroyed, arterioles sharply twisted, deformed, their lumen is uneven, venules dilated and deformed.